XPS study of impurities in Si‐doped AlN film. (12th May 2016) - Liang, F.; Chen, P.; Zhao, D. G.; Jiang, D. S.; Zhao, Z. J.; Liu, Z. S.; Zhu, J. J.; Yang, J.; Le, L. C.; Liu, W.; He, X.G.; Li, X. J.; et al.
Abstract : This paper reports an XPS study of impurities in a 100‐nm‐thick AlN film grown by metalorganic chemical vapor deposition (MOCVD) under low pressure on the n‐type 6H‐SiC substrate. The Si‐doped AlN film was characterized by the X‐ray photoelectron spectroscopy (XPS) in a high vacuum system, which reveals the content distribution and chemical states of impurities along depth. The XPS analysis of AlN film before and after argon‐ion etching indicates that there always exist Ga, O and C contaminations in AlN film. Especially, O contamination on the AlN film surface is mostly introduced during the growth of AlN layer by MOCVD. Meanwhile, most of O atoms bind with Al or Ga in Al―O and Ga―O chemical states. In particular, the Ga atoms in AlN film are always in two chemical states, i.e. Ga―Ga bond and Ga―O bond, which demonstrates that the aggregation of Ga is accompanying with AlN growth. Copyright © 2016 John Wiley & Sons, Ltd.